2009
DOI: 10.1007/s11227-009-0317-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutually independent Hamiltonian cycles in dual-cubes

Abstract: The hypercube family Q n is one of the most well-known interconnection networks in parallel computers. With Q n , dual-cube networks, denoted by DC n , was introduced and shown to be a (n + 1)-regular, vertex symmetric graph with some fault-tolerant Hamiltonian properties. In addition, DC n 's are shown to be superior to Q n 's in many aspects. In this article, we will prove that the n-dimensional dual-cube DC n contains n + 1 mutually independent Hamiltonian cycles for n ≥ 2. More specifically, let v i ∈ V (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In particular, hierarchical interconnection networks (HINs) have proven very popular. Amongst those, dual-cubes (Li et al, 2004) are actively researched: as examples, Zhou et al (2012a) discussed dual-cube conditional fault diagnosability, and Shih et al (2010) give a constructive proof of the existence of Hamiltonian cycles in dual-cubes.…”
Section: State Of the Artmentioning
confidence: 99%
“…In particular, hierarchical interconnection networks (HINs) have proven very popular. Amongst those, dual-cubes (Li et al, 2004) are actively researched: as examples, Zhou et al (2012a) discussed dual-cube conditional fault diagnosability, and Shih et al (2010) give a constructive proof of the existence of Hamiltonian cycles in dual-cubes.…”
Section: State Of the Artmentioning
confidence: 99%
“…Lai and Tsai [26] obtained the vertex bipancyclicity of dual-cube, and showed that dual-cube is bipancyclic even if it has up to n − 1 faulty edges. Shih et al [41] proved the existence of n + 1 mutually independent hamiltonian cycles in dual-cube. Let S 2 be the symmetric group of order 2, and Z 2 be the cyclic group of order 2.…”
Section: Definition 2 [8]mentioning
confidence: 99%
“…Not only are hypercubes popular as interconnection network on their own, but they are also very popular as seed for advanced network topologies such as those employed by hierarchical interconnection networks (HINs). Hierarchical hypercubes [4,5,6,7], hierarchical cubic networks [8,9,10], metacubes [11,12], dual-cubes [13,14] are some examples.…”
Section: Introductionmentioning
confidence: 99%